DEVELOPING CULTURALLY RESPONSIVE ENGLISH E-BOOKS USING SPEECH ACT THEORY FOR YOUNG EFL LEARNERS - Irfan Hamonangan Tarihoran; Sartika; Iwan Jazadi (University of Kuningan, 2025)
This study explores the application of speech act theory in the development of culturally responsive English-language e-books for young EFL learners. Employing a modified Research and Development (R&D) methodology, ten short stories rooted in Sumbawanese cultural themes were created by novice authors and iteratively refined through expert validation and learner feedback. Dialogues were constructed using Searle’s five illocutionary types, with representative and directive acts emerging as the most dominant. Initial field trials revealed that indirect speech acts hindered reader comprehension, prompting revisions toward more direct and pragmatically transparent expressions. The revised e-books demonstrated marked improvements, with over 85% of participants accurately interpreting dialogue functions and moral messages. Embedding localized content enhanced learner engagement, supported cultural identity formation, and aligned with principles of culturally responsive pedagogy. These findings affirm that speech act-informed, culturally grounded materials can significantly improve pragmatic literacy and narrative comprehension in early-stage English language learning. The study offers practical insights for ELT practitioners and material developers aiming to integrate local culture and pragmatic awareness into language instruction.